2010
DOI: 10.1111/j.1360-0443.2010.02975.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐delivered interventions for alcohol and tobacco use: a meta‐analysis

Abstract: Findings of the meta-analysis suggest that minimal contact computer-delivered treatments that can be accessed via the internet may represent a cost-effective means of treating uncomplicated substance use and related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
232
4
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(250 citation statements)
references
References 50 publications
5
232
4
7
Order By: Relevance
“…Previous systematic reviews that evaluated e-interventions for alcohol misuse have generally found short-term benefits (13)(14)(15)(16)(17), but examination of maintenance of intervention effects is needed. Two recent systematic reviews have reported follow-up outcomes at 6 months or longer.…”
Section: Primary Funding Source-us Department Of Veterans Affairsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous systematic reviews that evaluated e-interventions for alcohol misuse have generally found short-term benefits (13)(14)(15)(16)(17), but examination of maintenance of intervention effects is needed. Two recent systematic reviews have reported follow-up outcomes at 6 months or longer.…”
Section: Primary Funding Source-us Department Of Veterans Affairsmentioning
confidence: 99%
“…However, they did not analyze college student and noncollege adult trials separately (13,17), despite distinctions between these groups in patterns of alcohol consumption and associated impairment (18,19). In addition, previous systematic reviews have generally not reported on the efficacy of e-interventions for AUDs (13)(14)(15)(16)(17) or provided detailed descriptions of treatment intensity, including amount and type of human support (13)(14)17).…”
Section: Primary Funding Source-us Department Of Veterans Affairsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be mentioned that web-based education include some limitations and demerits, such as learners low level of knowledge on computers, lack of equipment and infrastructure, technology limitations and no access to the internet, problems with the internet bandwidth, and also problems with learner assessment (5). Though, considering huge number of merits mentioned on that, it seems to be efficient to plan preventive interventions for risky behaviors (6)(7)(8)(9)(10)(11). For example, Lockyer et al in their study on e-learning indicated that web-based education for HIV prevention is more effective compared with face-to-face classroom education (6).…”
Section: Dear Editormentioning
confidence: 99%
“…The internet offers the advantage of being available independent of location and time. Studies demonstrate that addiction specific internet based interventions can in principle bring about positive behavioural changes [13][14][15] and appear suitable for persons who would not normally use assistive and advisory services [14,[16][17]. Since pregnant women now inform themselves mainly through the internet [18,19] a new counselling approach in the form of an individualised, risk adapted internet based intervention to reduce alcohol and tobacco consumption in pregnant women ("IRIS") should be trialled which offers the advantage of good time and cost economical accessibility as well as interactive, anonymous exchange in contrast to the disclosure situation of contact with physicians.…”
mentioning
confidence: 99%